Plant growth regulator based product development for increase in rice yield - Sinniah, Uma Rani; Mustaza, Farid Nazrin; Ibrahim, Syazreena; Jaafar, Hawa Z. E.; Muhamad Awang, Rita; Tan, Chuan Ou (Knowledge Transfer Programme, 2017)
Reducing losses are one way of improving the yield in rice production. Lodging for example can cause up to 40% losses of rice production. Research shows that the use of plant growth regulators can reduce yield losses by improving susceptibility to lodging. However, due to its nature, plant growth regulators need to be used at the suitable plant growth stage with the optimum concentration to ensure its effectiveness. An established outcome from a research shows that the exogenous application of plant growth regulator helps in reducing lodging, thus improve the yield of rice. Importantly the plant growth regulator has to be formulated for adoption by the farmers. Through the construction of formulation using the phase diagram, handling and effectiveness of plant growth regulators can be improved, providing ease of work for the rice growers. This project is designed to transfer knowledge on plant growth regulators and formulation construction to the industry partner, Agrow Synergy Sdn Bhd. The knowledge transfer resulted in the establishment of a suitable formulation of plant growth regulator to be supplied to the farmers. In addition, the knowledge obtained by the industry will enable them to produce other agriculture related formulations based on the principles transferred in this project.